Pelatihan Pembuatan Aksesoris dan Souvenir Pernikahan Pada Masyarakat di Kabupaten Semarang - Mien Zyahratil Umami; Ariyana Damayanti (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
This community service activity was carried out in order to provide additional skills in making wedding souvenirs for delivery organizers. The aim of this activity is to increase knowledge, understanding and skills regarding the manufacture of delivery accessories for delivery management business groups in Semarang district. The results of observations that the author obtained in Semarang Regency are that there are many housewives who have great motivation to be able to have skills but do not yet understand what to do, so that they can be used as provisions to open and develop their business. Through training in making various decorative accessories and wedding souvenirs, they have the opportunity to open a business as an effort to improve their entrepreneurial skills in accepting orders for making wedding souvenirs to improve family welfare. In order to increase women's empowerment in entrepreneurship, it is necessary to provide training in making wedding accessories and souvenirs as well as skills in arranging gifts. This training activity uses interactive lecture methods, practice, question and answer and product evaluation. It is necessary to have knowledge about making accessories and souvenirs, as a business development effort. Therefore, making accessories and souvenirs is very necessary for everyone, not only to increase knowledge but also to increase motivation and increase self-confidence in opening a business.